Distribution of rocks in Pınarbaşı Ophiolite from central Anatolia (Turkey) based on analysis of ASTER and Landsat‐8 data. (20th April 2020) - Çörtük, Rahmi Melih; Çelik, Ömer Faruk; Alkan, Anıl; Özkan, Mutlu; Özyavaş, Aziz
Abstract : The Late Cretaceous Pınarbaşı Ophiolite (PO), located at central Turkey is represented by distinct rock types (e.g., harzburgite, dunite, pyroxenite, gabbro) that can be observed in many ophiolites around the world. In this study, the classification of rock types of PO in the Eastern Tauride Belt (Turkey) was made using the advanced spaceborne thermal emission and reflection radiometer and Landsat‐8 satellite images. The developed colour–band ratio composite images together with principal component analysis and minimum noise fraction transformations implemented to the remote sensing data efficiently delineate the spatial distribution of pyroxenites, metamorphic sole rocks, and gabbros in the study area. In addition, a body of serpentinized dunites, pyroxenites, metamorphic sole rocks, and listwaenites that has not been recognized before was identified within PO using remote sensing techniques. The promising results of the image processing were verified by detailed field observations and petrographic analysis. The satellite‐based remote sensing approaches of this work can be applicable for mapping ophiolitic rock types in PO in particular as well as other ophiolites from similar geographical regions around the world.